PROBLEMATIKA KARAKTER PESERTA DIDIK DI SEKOLAH DASAR INPRES 2 BAINA’A KECAMATAN SIDOAN KABUPATEN PARIGI - Sakina Sakina; Amilin A. Bulungo (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The purpose of this study is to find out the character problems of students at Inpres 2 Baina'a Elementary School, Sidoan District, Parigi Moutong Regency. Method of this study is qualitative in the form of field research, research data is collected through observation, interviews, and documentation. Analysis with the process of data reduction analysis and data presentation. Based on the results of the study it was found that in general, the problems with the character of students, namely, lack of discipline, low motivation to learn, lack of independence and honesty in learning and lack of social care and love for the environment that students have